2004
DOI: 10.1111/j.1471-4159.2004.02823.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor stimulation promotes the proliferation of cells derived from the post‐natal subventricular zone

Abstract: In the adult mammalian brain, neural stem cells persist in the subventricular zone (SVZ) where dopamine D 3 receptors are expressed. Here, we demonstrate that addition of 1 lM apomorphine increases cell numbers in post-natal SVZ cell cultures. This effect was prevented by a co-treatment with haloperidol, sulpiride or U-99194A, a D 3 -preferring antagonist, and mimicked by the dopamine D 3 receptor selective agonist 7-hydroxy-dipropylaminotetralin (7-OH-DPAT). EC 50 values were 4.04 ± 1.54 nM for apomorphine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 34 publications
3
63
2
2
Order By: Relevance
“…The preferential dopamine D 3 receptor agonist 7-hydroxy-N, N-di-n-propyl-2-aminotetralin (7-OH-DPAT) was selected for this proposal based on previous studies demonstrating its mitogenic role both in vitro (Pilon et al, 1994;Coronas et al, 2004) and in vivo (Van Kampen et al, 2004;Van Kampen and Robertson, 2005). Thus, 4 weeks after intoxication (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preferential dopamine D 3 receptor agonist 7-hydroxy-N, N-di-n-propyl-2-aminotetralin (7-OH-DPAT) was selected for this proposal based on previous studies demonstrating its mitogenic role both in vitro (Pilon et al, 1994;Coronas et al, 2004) and in vivo (Van Kampen et al, 2004;Van Kampen and Robertson, 2005). Thus, 4 weeks after intoxication (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the dopamine D 3 receptor appears to play an important role in neural development and shows a persistent expression through adulthood in the proliferative SVZ (Diaz et al, 1997). Furthermore, pharmacological stimulation of D 3 receptors promotes proliferation and neuronal differentiation of adult SVZ cells, both in vitro (Coronas et al, 2004) and in vivo (Van Kampen et al, 2004), whereas activation of other dopamine receptor subtypes does not (Coronas et al, 2004;Van Kampen et al, 2004;Kippin et al, 2005). Removal of dopaminergic afferents reduces SVZ proliferation (Baker et al, 2004;Höglinger et al, 2004), an effect reversed by a dopamine D 3 receptor agonist (Höglinger et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this, studies have shown that the relatively non-selective dopamine agonists, bromocriptine and apomorphine, act to stimulate adult rat SVZ-neurosphere proliferation, an effect that can be blocked by the D2L antagonist sulpiride. 14,22 Moreover, the highly selective D3 agonist 7-OH-DPAT, 22 has also been shown to have similar effects with neurosphere proliferation in vitro. However, the D1L agonist SKF 38393 has been shown to have no effect on proliferation in vitro.…”
Section: Dopaminergic Control Of Svz Cell Proliferation In Vitro and mentioning
confidence: 99%
“…Because damaged neurons can be labeled with BrdU (Coronas et al, 2004;Hoglinger et al, 2004), we do not rule out the possibility that severe injury induced by the MPTP might promote the nonspecific BrdU labeling in injured neurons. Furthermore, it is known that the fusion of neurons with cells expressing BrdU can produce double labeling of BrdU and neuronal markers in a cell without actual adult neurogenesis (El-Khodor et al, 2003).…”
Section: Discussionmentioning
confidence: 99%